An Assessment on Hounslow Heath Heavy Metal Contaminated Land Soil Quality and a Recommendation of a Primary School Location Chosen. Issue 4 (February 2020) - Zhang, Han
Abstract: This report will deal with the following aspects of Hounslow Heath contaminated land potential soil issues such as heavy metal containment. Meanwhile, it will give a recommendation on primary school location chosen in this region after comprehensive assessments. Firstly, backgrounds of contaminated land and Hounslow Heath will be briefly introduced, then the significances of those two factors will be identified, which includes the risk of reusing contaminated land and the difference between Hounslow Heath and other habitats. By telling the significances, the purpose of this part in the report is to discuss the value of Hounslow Heath, which is recognized as contaminated land because of historical landfill. In order to reuse this site, the contaminated land assessment is necessary under risk assessment regulation. After then, an analysis of Hounslow Heath, sampling points and methodology used will be presented, followed by data analysis, results will be motioned for further discussion.